MEDIA PEMBELAJARAN HURUF HIJAIYAH UNTUK ANAK USIA DINI BERBASIS GAME ANDROID - Ahmad Turmudi Zy; Edora Edora (Akademika : Jurnal Teknologi Pendidikan, 2022)
As religious people we must fortify ourselves as early as possible with the provision of religious knowledge. One of them is in reading the Koran. For early childhood, the initial stage of reading the Koran is being able to master the hijaiyah letters. The problem in this research is the lack of interest in children's learning and the lack of media that is applied in the process of learning hijaiyah letters. The media used is still conventional so that the learning objectives are not achieved optimally. Therefore, a learning media for early childhood was made in the form of an Android-based educational game. This research applies the MDLC (Multimedia Development Life Cyrcle) method. Testing the functional requirements in this application through the stages of black box testing. The black box test results are 100%, meaning that this application is in line with user needs and all functions run according to functional requirements. Therefore, it can be concluded that this educational game is attractive and effective in increasing hijaiyah letter learning skills